Analysis Effectiveness Sipd In Regional Development - Nurmayani; Ananda, Nelva; Salsabilah, Sabrina; View, Jessica Bi Yolanda; A.Sitorus, Mahza Dumoli; Irawan (CV Raskha Media Group, 2025)
Abstract:. The Regional Government Information System (Sistem Informasi Pemerintahan Daerah – SIPD) serves as an integrated system that supports local governments in carrying out planning, budgeting, and reporting processes. Through the implementation of SIPD, regional government data become more integrated, enabling resource management to be conducted in a transparent and accountable manner in order to achieve more effective regional development. Based on Ministry of Home Affairs Regulation Number 77 of 2020 concerning the Technical Guidelines for Regional Financial Management, the management of regional finances is required to be carried out through information systems covering the stages of planning, budgeting, implementation, administration, reporting, and accountability. This study aims to analyze the extent to which SIPD is utilized and accepted by users, as well as to assess its effectiveness by examining in depth the value of its benefits for the central government in terms of data integration, for local governments in accelerating development processes, and for the public in enhancing transparency of public services. Using a descriptive qualitative method based on a review of relevant literature, this study applies the Technology Acceptance Model (TAM) as its analytical framework. The expected results are to describe the role of SIPD in accelerating regional development and optimizing data integration among the central government, local governments, and the community